Konseling Multikultural dalam Mengatasi Konflik Antar Siswa Berbeda Latar Belakang Budaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Multicultural counseling in schools serves as an essential strategy to reduce conflicts and foster cultural awareness among students. Counselors play a central role by developing their own cultural competence, facilitating students’ reflection on their cultural identities, providing education on stereotypes and biases, creating safe spaces for cross-cultural dialogue, and strengthening institutional capacity through collaboration with teachers and parents. This counseling strategy emphasizes understanding the values, norms, and power dynamics of each cultural group to ensure interventions are both effective and culturally sensitive. An inclusive learning environment supports this process by offering written policies, curricula that reflect diversity, dialogue forums, and cross-cultural activities. The evaluation process involves establishing clear objectives, quantitative and qualitative indicators, and mixed methods, including surveys, discussions, and direct observations, with participation from counselors, teachers, principals, parents, and student representatives. Local adaptation of instruments, continuous monitoring, and systematic documentation ensure data validity and the sustainability of behavioral changes. Evaluation results form the basis for concrete recommendations, such as counselor training, inclusive curriculum development, and programs to strengthen cross-cultural relationships. This approach enables schools to cultivate a culture of empathy, understanding, and harmony, thereby enhancing relationships among students from diverse backgrounds.